I make the case like this $P(6)=P(E)P(E)P(E)+P(E)P(E)P(O)P(O)+P(E)P(O)P(O)P(O)P(O)+P(O)P(O)P(O)P(O)P(O)P(O)$

for $P(E)=\frac{3}{6}=\frac{1}{2}$ and $P(O)=\frac{3}{6}=\frac{1}{2}$

So,$P(6)=\frac{1}{2}\frac{1}{2}\frac{1}{2}+\frac{1}{2}\frac{1}{2}\frac{1}{2}\frac{1}{2}+\frac{1}{2}\frac{1}{2}\frac{1}{2}\frac{1}{2}\frac{1}{2}+\frac{1}{2}\frac{1}{2}\frac{1}{2}\frac{1}{2}\frac{1}{2}\frac{1}{2}$

$P(6)=\frac{1}{2^{3}}+\frac{1}{2^{4}}+\frac{1}{2^{5}}+\frac{1}{2^{6}}$

$P(6)=\frac{14}{64}$

but answer is $\frac{43}{64}??$

for $P(E)=\frac{3}{6}=\frac{1}{2}$ and $P(O)=\frac{3}{6}=\frac{1}{2}$

So,$P(6)=\frac{1}{2}\frac{1}{2}\frac{1}{2}+\frac{1}{2}\frac{1}{2}\frac{1}{2}\frac{1}{2}+\frac{1}{2}\frac{1}{2}\frac{1}{2}\frac{1}{2}\frac{1}{2}+\frac{1}{2}\frac{1}{2}\frac{1}{2}\frac{1}{2}\frac{1}{2}\frac{1}{2}$

$P(6)=\frac{1}{2^{3}}+\frac{1}{2^{4}}+\frac{1}{2^{5}}+\frac{1}{2^{6}}$

$P(6)=\frac{14}{64}$

but answer is $\frac{43}{64}??$